1976
DOI: 10.1139/v76-158
|View full text |Cite
|
Sign up to set email alerts
|

Structure de la mycosporine (P 310)

Abstract: Chern. 54, 1105Chern. 54, (1976. The structure 1 (2-rnethoxy-3-bis(hydroxyrnethyl)rnethylarnin~5-hydroxy-5-hydroxyrnethyl-2-cyclohexen-1-one has been attributed to rnycosporine (P. 310), a product isolated from Stereum Iiirsutum (Willd. ex Fr.) Fr.; this result is derived from the uv, ir, ms, and nrnr of IH and 13C spectral analysis of the natural product and its derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 5 publications
2
42
0
2
Order By: Relevance
“…The mycosporine-like amino acids (MAAs) are condensation derivatives of a cyclohexenone ring and amino acid or imino alcohol residues (65). Based on the characteristics of UV absorption by MAAs, several studies have suggested that these compounds can act as natural screens of UV radiation and should be considered photoprotectants (66,67).…”
Section: Raman Spectrometry Of Microbial Pigments-pure Culture Studiesmentioning
confidence: 99%
“…The mycosporine-like amino acids (MAAs) are condensation derivatives of a cyclohexenone ring and amino acid or imino alcohol residues (65). Based on the characteristics of UV absorption by MAAs, several studies have suggested that these compounds can act as natural screens of UV radiation and should be considered photoprotectants (66,67).…”
Section: Raman Spectrometry Of Microbial Pigments-pure Culture Studiesmentioning
confidence: 99%
“…Mycosporines were first discovered in terrestrial fungi (Favre-Bonvin et al 1976) and these metabolites are believed to provide UV protection to fungal spores while exposed to solar radiation during atmospheric dispersal (Young and Patterson 1982). Fungal metabolites strongly absorbing UV-B (λ max 310 nm), first described by Leach (1965) and notionally designated P-310, were present in the mycelia of several genera when sporulation had been induced with near-UV radiation, but were absent from nonsporulating colonies grown in darkness.…”
Section: Fungus and Lichen Mycobiontsmentioning
confidence: 99%
“…Mycosporine is the generic name given to water-soluble, UV-absorbing fungal metabolites with a cyclohexenone chromophore conjugated with the nitrogen substituent of an amino acid or amino alcohol (Favre-Bonvin et al 1976, Arpin andBouillant 1981) (Fig. 1 like amino acids from marine organisms are imino-carbonyl derivatives of the mycosporine cyclohexenone chromophore.…”
Section: Introductionmentioning
confidence: 99%